Nephrotoxicity in chronic low dose organophosphate exposure - Aung, Sanda; Abdullah, Nor Zamzila; A.Talib, Norlelawati; Mohd Noor, Noriah; Harun, Norra; Zainone, Zamzuria Mat; Abdul Razak, Tariq (2016)
Objectives: People are exposed to chronic low dose organophosphates (OPs) pesticides through agriculture and pest control activities. Apparently, there were significant epidemiological reports suggesting pesticides role in chronic kidney disease. This observation is yet to be confirmed with appropriate experimental model of chronic OPs exposure on animals. Thus, the aim of this study is to observe for histomorphological characteristics related to nephropathy in the kidneys of rats upon exposure to chronic low dose OPs. Materials and Methods: 24 males Sprague-Dawley rats were randomly divided into 3 groups of 6 rats each with Group 1 as a Control group, whilst Group 2 and Group 3 received subcutaneous vehicle (3% dimethyl sulphoxide + 97% v/v soy oil) and 18.0 mg/kg BW chlorpyrifos respectively, every other day for 180 days. After treatment, the rats were sacrificed and the right kidney was subjected to routine H&E examination and specific Masson-Trichrome and periodic-acid Schiff stain. Results: OPs exposed group (Group 3) exhibited significant histo-morphological abnormalities suggesting cell injury, apoptosis and degenerative changes in glomeruli and tubules. In contrast, the control groups 1 and 2 (vehicle) are spared. Conclusion: Chronic low dose OPs exposure induced nephrotoxicity. The exact mechanism of nephrotoxicity should be further investigated. Keywords: